2003
DOI: 10.1021/jp026208j
|View full text |Cite
|
Sign up to set email alerts
|

A Dipole Interaction Model for the Molecular Second Hyperpolarizability

Abstract: A dipole interaction model (IM) for calculating the molecular second hyperpolarizability, γ, of aliphatic and aromatic molecules has been investigated. The model has been parametrized from quantum chemical calculations of γ at the self-consistent field (SCF) level of theory for 72 molecules. The model consists of three parameters for each element p:  an atomic polarizability, an atomic second hyperpolarizability, and an atomic parameter, Φp, describing the width of the atomic charge distribution. The Φp parame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
59
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(59 citation statements)
references
References 116 publications
0
59
0
Order By: Relevance
“…3, it is observed that contributor [1,1] always gives the greatest contribution to the total scattering, except for incoming photon wavelengths approaching 20 m; then all contributors are equivalent. Note that the line [1,2] includes the result for RS 12  and RS 21  ; accordingly contributor [1,2] features a contribution twice the value of the two 'diagonal' contributions at high photonic wavelengths. It is also observed that [1,2] is the only term that may have a negative value -but this is apparent only at photon energies greater than 0 u E .…”
Section: Rayleigh Scatteringmentioning
confidence: 99%
See 3 more Smart Citations
“…3, it is observed that contributor [1,1] always gives the greatest contribution to the total scattering, except for incoming photon wavelengths approaching 20 m; then all contributors are equivalent. Note that the line [1,2] includes the result for RS 12  and RS 21  ; accordingly contributor [1,2] features a contribution twice the value of the two 'diagonal' contributions at high photonic wavelengths. It is also observed that [1,2] is the only term that may have a negative value -but this is apparent only at photon energies greater than 0 u E .…”
Section: Rayleigh Scatteringmentioning
confidence: 99%
“…Normalising the relative values by reference to the total rate (of elastic scattering, in this instance), only the individual polarizability contributions are of importance as other factors cancel in the ratios. Thus we secure the following expression, written in terms of (1)  and (2)  from which the three contribution ratios of Rayleigh scattering are generated;…”
Section: Rayleigh Scatteringmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, they are important in the development of the future generations of communication systems and computers, and much effort has been devoted to increasing the useful non linearity of optical mate-rials [1] [2]. Depending on the particular application, the use of organic materials may offer majored vantages over conventional inorganic crystals [3] [4].…”
Section: Introductionmentioning
confidence: 99%